Penerapan Arsitektur Modern Fungsionalisme Pada Rancangan Hotel Kapsul Di Toraja - Pratama, Wahyu; Nursyam, Nursyam; Oktawati, Andi Eka (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Functionalism Modern architecture has the principle that building design must be based on the purpose and function of the building itself. Modern architecture prioritizes a position where architecture can accommodate various activities and the use of reinforced concrete and steel. The characteristics of the contemporary functionalist architectural concept include designing buildings that are pure without decoration and have simple shapes such as planes, boxes and cubes. Capsule hotel in Toraja, with a modern functionalist architectural approach, designed in the city of Rantepao, the center of Toraja, and easy to reach by public and private transportation. The design of this hotel aims to provide lodging facilities for tourists holidaying in Toraja, a popular tourist destination, especially in South Sulawesi; This is influenced by the uniqueness of its culture and customs, especially its natural beauty. Before identifying the capsule hotel design, the author carried out a research methodology, namely a qualitative descriptive methodology. Referring to the explanation above, how to apply modern functionalist architecture to a capsule hotel designed in Toraja so that you can identify the application of modern functionalist architectural elements in the design. The results of the analysis of the application of functionalist architecture to capsule hotel design in Toraja can be seen in the building form, structural system, spatial layout and materials.